PENGARUH LEVERAGE, RETURN ON EQUITY (ROE), DAN FIRM SIZE TERHADAP FIRM VALUE DENGAN DIVIDEND POLICY SEBAGAI VARIABEL INTERVENING - Suci Atiningsih; Nurul Latifah Pancawardani; Mohklas Mohklas (STIE Pelita Nusantara Semarang, 2020)
This study aims to determine the effect of leverage, return on equity (ROE), and firm size on firm value with dividend policy as an intervening variable.Data analysis methods to test hypotheses using Path Analysis Methods. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in the period 2012-2017. The samples in this study were determined by purposive sampling, so that the number of companies obtained was 44 companies with 264 samples.The results show that leverage has a negative and significant effect on dividend policy. Return on equity (ROE) has no significant effect on dividend policy. Firm size has a positive and significant effect on dividend policy. Dividend policy, return on equity (ROE), and firm size have a positive and significant effect on firm value. Leverage does not have a significant effect on firm value. Dividend policy cannot mediate the effect of leverage, return on equity (ROE) and firm size on firm value